Patient Satisfaction with an Australian Digital Weight-Loss Service: A Comparative Retrospective Analysis - Louis Talay; Matt Vickers; Sally Wu (Telemedicine Reports)
Objective: This study compared the experiences of patients who received proactive coaching through a digital weight-loss service (DWLS) with those who received reactive coaching. Methods: Patients (n = 100) were emailed a mixed-methods survey after 8 weeks of participation in the Juniper DWLS. Reactive and proactive group responses to the survey’s five Likert-scale questions were compared through Mann–Whitney U tests. A Braun and Clarke thematic analysis was conducted on responses to the survey’s open-ended question. Results: Proactive group patients were statistically significantly more likely than reactive coaching patients to find their health coach helpful and less likely to feel that their health coach did not communicate with them enough. Generally, patients felt that Juniper health coaching needed to be more personalized and proactive. Discussion: This research adds vital foundational knowledge to the scarce literature on real-world comprehensive DWLSs, highlighting the importance of patient preferences around care continuity.